A randomised controlled trial of 7.5‐mm and 7.0‐mm tracheal tubes vs. 6.5‐mm and 6.0‐mm tracheal tubes for men and women during laparoscopic surgery. (17th August 2021) - Cho, H. Y.; Yang, S. M.; Jung, C. W.; Cheun, H.; Lee, H. C.; Park, H. P.; Yoon, H. K.
Summary: Sore throat after tracheal intubation impairs postoperative recovery. We randomly allocated 172 ASA physical status 1–2 participants, scheduled for laparoscopic lower abdominal surgery, to tracheal intubation with larger tubes (n = 88) or smaller tubes (n = 84), with internal diameters 7.5‐mm vs. 6.5‐mm for men and 7.0‐mm vs. 6.0‐mm for women. Primary outcome was the rates of no, mild, moderate or severe sore throat 1 h after surgery, which were 60, 10, 17 and 1 with larger tracheal tubes and 79, 5, 0 and 0 with smaller tubes, p < 0.001. The equivalent rates 24 h after surgery were 64, 16, 8 and 0 vs. 74, 6, 3 and 1, p = 0.037. Intra‐operative ventilatory variables were unaffected by tube diameter, including peak inspiratory pressure, plateau pressure and end‐tidal carbon dioxide partial pressure. In summary, smaller tracheal tubes benefitted patients having laparoscopic operations.